Investigating the relationship between social stigma and treatment adherence in type 2 diabetes patients at healthcare centers in Northwest Iran - Maryam Sedaei; Mohammad Ail Mohamadi; Behrouz Dadkhah (BMC Public Health)
Abstract Background The social stigma associated with type 2 diabetes is a significant global mental and social health issue that can hinder treatment adherence among patients. To address this concern, the present study aimed to examine the relationship between social stigma and treatment adherence levels in type 2 diabetes patients attending healthcare centers in northwest Iran. Methods In this descriptive-correlation study, 432 patients with type 2 diabetes referred to Ardabil city health service centers were selected by simple random and multi-stage cluster method. The data collection tools included the personal-social profile form, type 2 diabetes stigma assessment scale (DSAS-2), and treatment adherence questionnaire. Data were analyzed using SPSS 26 software with descriptive statistics, independent t-tests, analysis of variance, a logistic linear regression model. Results The results indicated that the average score for the total social stigma of type 2 diabetes among the studied samples was 59.27 ± 15.52. A high level of perceived social stigma was observed in 55.6% of the patients. The average score for treatment adherence was 97.46 ± 28.79, with an adherence situation at an average level (59.7%). An inverse relationship was identified between the social stigma of diabetes and adherence to treatment (r = -0.29, p < 0.001). Additionally, there was a significant relationship between the average score of social stigma of diabetes and variables such as gender and marital status, as well as between the average score of treatment adherence and the gender of patients. The stepwise multiple linear regression model revealed that 15.1% of the variance in treatment adherence could be explained by age, duration of the disease, and social stigma of diabetes. Conclusion The study found that, more than half of the patients had social stigma and reported their adherence to treatment as moderate. Also, there was an inverse and significant correlation between social stigma and treatment adherence. Therefore, it is necessary to provide psychological counseling services to reduce social stigma and teach the importance of adherence to treatment in these patients.